A Critical Review on Hydrogen Evolution Electrocatalysis: Re-exploring the Volcano-relationship - Zeradjanin, Aleksandar R.; Grote, Jan-Philipp; Polymeros, George; Mayrhofer, Karl (Electroanalysis, 2016)
The "volcano"-relationship for the electrocatalytic hydrogen evolution reaction seems to be a generally accepted phenomenology in electrochemistry. Based on the Sabatier principle, which suggests a not too strong, nor too weak binding of reaction intermediates as prerequisite for high reaction rates, it provides a straightforward and intuitive explanation for a plethora of experimental results. However, while the Sabatier principle as a main paradigm of heterogeneous catalysis was never really disputed in the case of gas-phase reactions, it remains questionable if it can be the main driving principle that governs activity trends of electrocatalytic reactions. This work provides an overview on this topic for the model hydrogen evolution reaction (HER), pointing out certain inconsistencies and contradictions found in literature. The critical assessment provides a viewpoint which could have important practical consequences and could provide different perspective on future catalyst design.
Keywords: hydrogen evolution; activity trends; "volcano"-relationship; electrocatalysis